We have two equations

`sqrt(x)+sqrt(y) = 16` --------->1

`x -y = -128` --------->2

we can rewrite 2 as,

`(sqrt(x)+sqrt(y))(sqrt(x)-sqrt(y)) = -128`

16(sqrt(x)-sqrt(y)) =-128

`sqrt(x)-sqrt(y) = -8` we shall call this equation as 3.

Now if we add 1 to 3 you get,

`2sqrt(x) = 16 -8 = 8`

sqrt(x) =...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have two equations

`sqrt(x)+sqrt(y) = 16` --------->1

`x -y = -128` --------->2

we can rewrite 2 as,

`(sqrt(x)+sqrt(y))(sqrt(x)-sqrt(y)) = -128`

16(sqrt(x)-sqrt(y)) =-128

`sqrt(x)-sqrt(y) = -8` we shall call this equation as 3.

Now if we add 1 to 3 you get,

`2sqrt(x) = 16 -8 = 8`

sqrt(x) = 4

x = 16.

then substituting 2, you get,

16-y=-128

y = 16+128 = 144.

Therfore answer is x= 16 and y = 144.